Taxonomic note on the endemic genus Lophopogon (Poaceae: Andropogoneae) from India - Landge, Shahid Nawaz; Shinde, Rajendra D. (Phytotaxa, 2023)
Although the genus Lophopogon comprises only two distinct species, their identification has always been bewildering in some of the available grass literature in India. This confusion mainly stems from the tendency of Indian botanists to utilize weak key characters to differentiate the species. We have discussed both the variable as well as distinguishing features of the Lophopogon species and revised the key to make it more efficient. Upon a thorough morphological study of the recently described L. prasannae, we have concluded that it is but a variable form of an obscure species L. kingii. Therefore, we now consider it a new heterotypic synonym of the latter. While re-evaluating the previously misidentified specimens of Lophopogon, we have established two new distributional records of L. kingii for the states of Andhra Pradesh and Karnataka, South India. In L. kingii a characteristic whitish indumentum is observed, which is confined to the base of the plant and is not observed in any of the variable forms of L. tridentatus. Based on this character, we have restructured and simplified the identification key for easy and accurate species delimitation. We have also provided a brief discussion on the phenotypic variability of both the species, along with photo plates to facilitate identification and showcase a variability spectrum in plant habit. Distribution of L. kingii is plotted on the map based on the available specimens at BSI, BSID, CAL and K herbaria.